The state of science on severe air pollution episodes: Quantitative and qualitative analysis - Lidia Morawska; Tong Zhu; Nairui Liu; Mehdi Amouei Torkmahalleh; Maria de Fatima Andrade; Benjamin Barratt; Parya Broomandi; Giorgio Buonanno; Luis Carlos Belalcazar Ceron; Jianmin Chen; Yan Cheng; Greg Evans; et al. (Environment International, 2021)
Severe episodic air pollution blankets entire cities and regions and have a profound impact on humans and their activities. We compiled daily fine particle (PM2.5) data from 100 cities in five continents, investigated the trends of number, frequency, and duration of pollution episodes, and compared these with the baseline trend in air pollution. We showed that the factors contributing to these events are complex; however, long-term measures to abate emissions from all anthropogenic sources at all times is also the most efficient way to reduce the occurrence of severe air pollution events. In the short term, accurate forecasting systems of such events based on the meteorological conditions favouring their occurrence, together with effective emergency mitigation of anthropogenic sources, may lessen their magnitude and/or duration. However, there is no clear way of preventing events caused by natural sources affected by climate change, such as wildfires and desert dust outbreaks.